Dengue rapid diagnostic via surface plasmon resonance biosensor / Peyman Jahanshahi - Peyman, Jahanshahi (2015)
The aim of this thesis is to introduce an optical technique which can be utilized in detection of dengue virus rapidly. This technique involves the application of analytical and numerical electromagnetic simulations led by physical insight and theoretical knowledge. As a part of this study, the most common permittivity function models are compared and the best model is identified for the proposed biosensor structure. The best model (Brendel-Bormann) is found to have an accuracy of ~94.4% with respect to experimental data. On the other hand, Finite Element Method (FEM) is found to be a valuable tool in the numerical solutions of the proposed biosensor structure throughout this thesis. Beside of simulation, the experiment is implemented through the Biacore device which is based on the surface plasmon resonance (SPR) technique. According to the experimental results, a serum volume of only 1 μl from a dengue patient (as a minimized volume) is required to determine the ratio of each dengue serotype in samples with 83-93% sensitivity and 100% specificity. The Biacore device is considered in an effort to demonstrate a rapid diagnostic test of dengue virus and the application of the intended technique in this detection. An immobilization of dengue antigen is properly performed on the chip surface, and all samples in four serotypes of dengue virus are examined through the chip. Beside the determination of sensitivity and specificity of our detection method, an optimization of sample volume is studied with different concentrations of samples. In addition, the theoretical calculations are validated in comparison with experimental results. According to the sample from each category of dengue serotypes 2 (low, mid, and highly positive), the error ratio of ~5.35%, 6.54%, and 3.72% is obtained at the end.